Discovery of 2, 4-dimethoxypyridines as novel autophagy inhibitors. Issue 35 (30th August 2018) - Robke, Lucas; Rodrigues, Tiago; Schröder, Peter; Foley, Daniel J.; Bernardes, Gonçalo J.L.; Laraia, Luca; Waldmann, Herbert
Abstract: Autophagy is a catabolic process, which mediates degradation of cellular components and has important roles in health and disease. Therefore, small molecule modulators of autophagy are in great demand. Herein, we describe a phenotypic high-content screen for autophagy inhibitors, which led to the discovery of a dimethoxypyridine-based class of autophagy inhibitors, which derive from previously reported, natural product-inspired MAP4K4 inhibitors. Comprehensive structure-activity relationship studies led to a potent compound, and biological validation experiments indicated that the mode of action was upstream or independent of mTOR. Graphical abstract: